Multi‐scenario comprehensive benefit evaluation model of a multi‐energy micro‐grid based on the matter‐element extension model. Issue 3 (26th October 2020) - Liu, Hang; Shen, Weijie; He, Xinying; Zeng, Bo; Liu, Yingxin; Zeng, Ming; Zhao, Chaoyue
Abstract: Integrated energy systems and multi‐energy micro‐grids are complex multi‐agent collaborative optimization projects. According to the operating structure and characteristics of the multi‐energy system, considering the externality, economy and other factors, a scientific and effective comprehensive evaluation are important decision supports to ensure its implementation and promote its development. Therefore, this paper proposes a comprehensive benefit evaluation model of a multi‐energy micro‐grid based on the matter‐element extension model. With the research trends and practical requirements of multi‐energy micro‐grid benefit evaluation, an evaluation index system covering energy efficiency indicators, economic indicators, reliability indicators, and renewable energy consumption indicators has been constructed, and uncertainties have been resolved in cloud model and fuzzy set theory. Based on the advantages of the performance evaluation information, the system operation scenarios in the process of planning scheme formation are fully considered, and then a matter‐element‐extensible multi‐attribute decision‐making model is proposed to evaluate the comprehensive benefits of multi‐energy micro‐grids. Finally, the feasibility of the above method is verified by comparing the comprehensive benefit evaluation results of the multi‐energy micro‐grid under different planning scenarios. In addition, a certain decision‐making reference is provided for the formation of a multi‐energy micro‐grid configuration scheme. Abstract : With the objective of more dynamic and practical research on the energy efficiency evaluation of micro‐network requirements, we built an evaluation index system, including an index and an economy index of energy efficiency, reliability, and renewable energy, based on the cloud model and fuzzy set theory, which has the advantage of solving uncertainty evaluation information, while taking into account the running scene on the formation of the planning system. We proposed this based on the matter‐element extension of the multiple attribute decision‐making model to simulate the multi‐energy micro‐network comprehensive benefit evaluation. Finally, the feasibility of the above method is verified by comparing the comprehensive benefit evaluation results of the multi‐energy micro‐grid under different planning scenarios. In addition, a certain decision‐making reference is provided for the formation of a multi‐energy micro‐grid configuration scheme.